Limited Therapeutic Options in Mexico for the Treatment of Urinary Tract Infections - Guadalupe Miranda-Novales; Karen Flores-Moreno; Yolanda López-Vidal; Samuel Ponce de León-Rosales; PUCRA Network Members (MDPI AG, 2022)
The rise in antimicrobial resistance (AMR) has complicated the management of urinary tract infections (UTIs). The objective of this study was to evaluate the antimicrobial susceptibility patterns of Escherichia coli and Klebsiella pneumoniae. Design: prospective observational study. Bacteria were classified as susceptible or resistant to ampicillin-sulbactam, amikacin, gentamicin, ciprofloxacin, norfloxacin, nitrofurantoin, trimethoprim-sulfamethoxazole (TMP/SMZ), ertapenem, meropenem, and fosfomycin. The sensitivity to fosfomycin and chloramphenicol was evaluated by the disk diffusion method. Statistical analysis: the chi-square test and Fisher's exact test were used to compare differences between categories. A p value < 0.05 was considered statistically significant. Isolates were collected from January 2019 to November 2020 from 21 hospitals and laboratories. A total of 238 isolates were received: a total of 156 E. coli isolates and 82 K. pneumoniae isolates. The majority were community-acquired infections (64.1%). Resistance was >20% for beta-lactams, aminoglycosides, fluoroquinolones, and TMP/SMZ. For E. coli isolates, resistance was <20% for amikacin, fosfomycin, and nitrofurantoin; for K. pneumoniae, amikacin, fosfomycin, chloramphenicol, and norfloxacin. All were susceptible to carbapenems. K. pneumoniae isolates registered a higher proportion of extensively drug-resistant bacteria in comparison with E. coli (p = 0.0004). In total, multidrug-resistant bacteria represented 61% of all isolates. Isolates demonstrated high resistance to beta-lactams, fluoro-quinolones, and TMP/SMZ.